Cholinergic modulation of hippocampal network function - Teles-Grilo Ruivo, Leonor; Mellor, Jack (Frontiers in Synaptic Neuroscience, 2013)
Cholinergic septohippocampal projections from the medial septal area to the hippocampus are proposed to have important roles in cognition by modulating properties of the hippocampal network. However, the precise spatial and temporal profile of acetylcholine release in the hippocampus remains unclear making it difficult to define specific roles for cholinergic transmission in hippocampal dependent behaviours. This is partly due to a lack of tools enabling specific intervention in, and recording of, cholinergic transmission. Here, we review the organisation of septohippocampal cholinergic projections and hippocampal acetylcholine receptors as well as the role of cholinergic transmission in modulating cellular excitability, synaptic plasticity and rhythmic network oscillations. We point to a number of open questions that remain unanswered and discuss the potential for recently developed techniques to provide a radical reappraisal of the function of cholinergic inputs to the hippocampus.